LEMBAGA PENDIDIKAN ISLAM AKHIR ABAD XX Studi Pendidikan Muhammadiyah Sekolah Umum Plus dan Boarding School - Heni Listiana (TADRIS: Jurnal Pendidikan Islam, 2015)
Abstract: Modernization of Islamic education institutions in Indonesia was preceded by  Muhammadiyah movement that rised the idea of extra public schools or so called "HIS met de Qur'an". This school model became the forerunner of modern Islamic education institutions in the 20th century. This school model is, then, disseminated to other reformist movements. ‘Plus’ Public Schools  has become a new phenomenon of modern educational institutions to acomodate the needs of Muslims to modern education. In addition to the developing Extra Public Schools, Muhammadiyah also developed "boarding School" (Dormitory) education system which was initially criticized to address the needs of the Muslim community towards education. Keywords: islamic education institutions, muhammadiyah, 20th century